Electrophysiologically calibrated optogenetic stimulation of dentate granule cells mitigates dendritic spine loss in denervated organotypic entorhino-hippocampal slice cultures - Tijana Hanauske; Carolin Christina Koretz; Tassilo Jungenitz; Jochen Roeper; Alexander Drakew; Thomas Deller (Scientific Reports, 2025)
Abstract Organotypic slice cultures (OTCs) are versatile tools for studying long-term structure-function relationships of neurons within a defined network (e.g. hippocampus). We developed a method for repeated experimenter-controlled activation of hippocampal granule cells (GCs) in OTCs within the incubator. After several days of contact-free photonic stimulation, we were able to ameliorate entorhinal denervation-induced structural damage in GCs. To achieve this outcome, we had to calibrate the intensity and duration of optogenetic (light) pulses using whole-cell electrophysiological recordings and multi-cell calcium imaging. Our findings showed that ChR2-expressing cells generated action potentials (APs) or calcium transients in response to illumination but were otherwise functionally indistinguishable from non-transduced GCs within the same neural circuit. However, the threshold for AP firing in single GCs varied based on the stimulus light intensity and the expression levels of ChR2. This information allowed us to calibrate light intensity for chronic stimulations. Denervated GCs exhibited significant spine loss four days post-denervation, but this detrimental effect was mitigated when AP firing was induced at a physiological GC bursting rate. Phototoxic damage caused by chronic light exposure was significantly reduced if illuminated with longer wavelength and by adding antioxidants to the culture medium. Our study presents a versatile approach for concurrent non-invasive manipulation and observation of neural circuit activity and remodeling in vitro.